Assessment of Cas12a‐mediated gene editing efficiency in plants. Issue 10 (19th April 2019) - Bernabé‐Orts, Joan Miquel; Casas‐Rodrigo, Iván; Minguet, Eugenio G.; Landolfi, Viola; Garcia‐Carpintero, Victor; Gianoglio, Silvia; Vázquez‐Vilar, Marta; Granell, Antonio; Orzaez, Diego
Summary: The CRISPR/Cas12a editing system opens new possibilities for plant genome engineering. To obtain a comparative assessment of RNA‐guided endonuclease (RGEN) types in plants, we adapted the CRISPR/Cas12a system to the GoldenBraid (GB) modular cloning platform and compared the efficiency of Acidaminococcus (As) and Lachnospiraceae (Lb) Cas12a variants with the previously described GB‐assembled Streptococcus pyogenes Cas9 (SpCas9) constructs in eight Nicotiana benthamiana loci using transient expression. All three nucleases showed drastic target‐dependent differences in efficiency, with LbCas12 producing higher mutagenesis rates in five of the eight loci assayed, as estimated with the T7E1 endonuclease assay. Attempts to engineer crRNA direct repeat (DR) had little effect improving on‐target efficiency for AsCas12a and resulted deleterious in the case of LbCas12a. To complete the assessment of Cas12a activity, we carried out genome editing experiments in three different model plants, namely N. benthamiana, Solanum lycopersicum and Arabidopsis thaliana . For the latter, we also resequenced Cas12a‐free segregating T2 lines to assess possible off‐target effects. Our results showed that the mutagenesis footprint of Cas12a is enriched in deletions of −10 to −2 nucleotides and included in some instances complex rearrangements in the surroundings of the target sites. We found no evidence of off‐target mutations neither in related sequences nor somewhere else in the genome. Collectively, this study shows that LbCas12a is a viable alternative to SpCas9 for plant genome engineering.